Health Care Providers' Perceptions of Nutrition Support in Pediatric Oncology and Hematopoietic Stem Cell Transplant Patients. (July 2016) - Montgomery, Kathleen; Belongia, Meghan; Schulta, Christina; Mulberry, Mollie Haddigan; Nugent, Melodee L.; Simpson, Pippa M.
One of the most common side effects of medical treatment for patients with an oncologic diagnosis is malnutrition. There is limited research that broadly assesses the perceptions of health care providers (HCPs) regarding nutrition support in the pediatric population. The purpose of this study was to describe the perceptions of nutrition support among pediatric oncology and hematopoietic stem cell transplant HCPs. The study used a cross-sectional descriptive design using a 31-item survey. Results of the survey indicated that nurses were more likely to initiate conversations about nutrition support during the first month of diagnosis, while midlevel providers and physicians initiated discussions in response to a change in nutritional status evidenced by decreased oral intake or weight loss. Participants reported resistance by patients and families more often for enteral nutrition compared with parenteral nutrition. Findings suggest a need to develop a more unified service line–based approach for initiating discussions related to nutrition support that incorporate patient and family perceptions.